Preparation, Characterization, and In Vitro Evaluation of Parenteral Olanzapine Microspheres Loaded in Malaysian Mastic Polymer - Al-Haddad, Mohammed Gameel; Al-Tahami, Khaled; Othman, Gamil Qasem (Jocpr Publishing, 2020)
The purpose of this study is to develop and evaluate olanzapine microspheres fabricated from biodegradable Malaysia mastic polymer to prolong release. Olanzapine microspheres have been prepared by oil/water solvent vaporization method with biocompatible Malaysia mastic polymer in different ratios with drug. The prepared microspheres were assessed for morphology, density, syringability, suspendability, percent yield, drug encapsulation efficiency and drug/polymer compatibility. In-vitro release, isothermal balance and accelerated studies were also studied. The percent yields and drug encapsulation efficiency of various formulations were within the acceptable range. IR spectra display no interplay between olanzapine and polymer used. Scanning electron microscopy of formulated microspheres showed spherical shape particles with small particles size. The release profile of olanzapine from the various microspheres was prolonged over 600 hours and the release obeyed Peppas diffusion for all formulations with different value that comply with Fickian law and showed acceptable stability and shelf life of selected formula. It was concluded that the formulated olanzapine microspheres by Malaysia mastic polymer was confirmed probable candidate for harmless and effective prolonged microspheres. It also concluded that the ratio of polymer/drug had main role in prolongation and the optimum formula was MF1:6 in which the drug amount was double the amount of polymer.